GLOBAL TREND OF LOCAL TASTE: A CASE STUDY OF ALTERNATIVE FOOD CONSUMPTION IN BENGKULU - Syabrina Azahara; Andi Azhar (Pedagogic Research-Applied Literacy Journal, 2025)
This research aims to analyze the phenomenon of alternative food consumption in Bengkulu with a comprehensive approach, covering social, cultural, economic and environmental aspects. In the midst of globalization that brings new food trends, Bengkulu has great potential in developing alternative foods based on local raw materials that are rich in nutritional benefits and sustainability. This research uses a literature study method that relies on relevant written sources to dig up information and build a strong theoretical basis. Through this approach, it is hoped that an overview of consumer preferences for alternative foods can be found, as well as the factors that influence these choices. In addition, this research also seeks to identify opportunities and challenges in developing alternative foods that can compete in the global market without abandoninglocal cultural roots. The results of this study are expected to contribute to culinary industry players, government, and academics in formulating appropriate strategies to promote locally-based alternative foods, as well as increasing awareness of the importance of healthy and sustainable food consumption. Therefore, the development of alternative food in Bengkulu needs to be encouraged with more intensive education so that people are more aware of its benefits in supporting a healthy and environmentally friendly lifestyle.